Parental Attention to Important Factors in Cultivating Students Interest in Learning in Class III of SDN 105285 Tandem Hilir I Academic Year 2025/2026 - Wahyu Hidayat; Ahmad Zul Fadli (Universitas Islam Negeri Sumatera Utara, 2026)
Parental Attention is an Important Factor in Cultivating Student Interest in Learning in Grade III of SDN 105285 Tandem Hilir I, Academic Year 2025/2026. This study aims to determine how parental attention is an important factor in fostering student interest in learning in Grade III of SDN 105285 Tandem Hilir I in the 2025/2026 Academic Year. The background of this study is based on the low interest in learning among some students, which is suspected to be related to a lack of parental attention in the child's education process at home. The instruments used were interviews and documentation of parental attention and student interest in learning. This is demonstrated by students' desire to learn. Therefore, it can be concluded that the greater the parental attention, the greater the students' interest in learning. The implications of this study are expected to serve as a consideration for parents and schools to enhance collaboration in providing optimal attention to support increased student interest in learning.